2009
DOI: 10.3390/molecules14031111
|View full text |Cite
|
Sign up to set email alerts
|

Laser Photolysis and Thermolysis of Organic Selenides and Tellurides for Chemical Gas-phase Deposition of Nanostructured Materials

Abstract: Laser radiation-induced decomposition of gaseous organic selenides and tellurides resulting in chemical deposition of nanostructured materials on cold surfaces is reviewed with regard to the mechanism of the gas-phase decomposition and properties of the deposited materials. The laser photolysis and laser thermolysis of the Se and Te precursors leading to chalcogen deposition can also serve as a useful approach to nanostructured chalcogen composites and IVA group (Si, Ge, Sn) element chalcogenides provided that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…It is demonstrated that from such measurements it is possible (in conjunction with theoretical calculations) , to infer which excited states are involved in the photodissociation of H 2 Se in its first diffusive band. Finally, it should be noted that understanding the fate of photolyzed group VI compounds under conditions ranging from ices to metal deposition environments remains a challenge, and the current work lends insight into understanding the photolysis of such species.…”
Section: Introductionmentioning
confidence: 93%
“…It is demonstrated that from such measurements it is possible (in conjunction with theoretical calculations) , to infer which excited states are involved in the photodissociation of H 2 Se in its first diffusive band. Finally, it should be noted that understanding the fate of photolyzed group VI compounds under conditions ranging from ices to metal deposition environments remains a challenge, and the current work lends insight into understanding the photolysis of such species.…”
Section: Introductionmentioning
confidence: 93%